The Optimization of Fluid Management in Septic Shock Emergencies: A Hemodynamic-Based Approach: Optimization of Fluid Management in Septic Shock Emergencies: A Hemodynamic-Based Approach - Hutomo, Yugi Tri (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Sepsis is a medical emergency condition that can cause shock and multi-system organ failure. Proper management of fluid management in patients with sepsis shock is essential to prevent death. The purpose of this study is to optimize fluid management in patients with sepsis shock through a hemodynamics-based approach, as well as to evaluate its impact on clinical outcomes, including improvements in hemodynamic parameters and organ function. This study uses an observational study design with a retrospective approach. Univariate analysis showed that the application of hemodynamic-based fluid management successfully improved the hemodynamic parameters of patients, with a significant reduction in mortality rates and an increase in mean blood pressure. In contrast, patients who did not get hemodynamics-based fluid management showed longer symptoms of shock. In bivariate analysis, there was a significant relationship between the volume of fluid administered based on hemodynamic monitoring and improvement of organ function. Hemodynamic-based fluid management optimization in patients with septic shock has been shown to improve hemodynamic parameters, improve prognosis, and reduce mortality rates. This approach is recommended to be integrated in clinical practice in intensive care units to improve the quality of sepsis shock care.